ANALISIS PERBANDINGAN TEKNOLOGI DIGITAL DALAM TRANSFORMASI PILKADA: PELUANG DAN TANTANGAN - Insyira Yusdiawan Azhar; Robby Darwis Nasution; Jusuf Harsono (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2026)
This study examines the implementation of three digital platforms introduced by Indonesia’s General Elections Commission (KPU): the Logistics Information System (SiLog), the Voter Data System (Sidalih), and the Management Information System (SiMan). These platforms represent KPU’s efforts to modernize election administration through digital transformation. The objective of this research is to explore how each system functions, their respective roles, and the challenges encountered in promoting transparency, accountability, and operational efficiency in election management. The study employs a qualitative approach through a combination of literature analysis and interviews with key officials involved in electoral operations. Findings indicate that the three systems operate in an interconnected manner: Sidalih manages voter registration data, SiLog oversees the distribution of election logistics, and SiMan facilitates internal administrative coordination. Nonetheless, the study identifies persistent obstacles related to infrastructure limitations, uneven digital competence among personnel, and insufficient system integration. Overall, the digitalization of election management through SiLog, Sidalih, and SiMan contributes to strengthening the governance of electoral processes in Indonesia, though further improvements in technical capacity and institutional coordination remain essential for achieving optimal performance.